Is my “red” your “red”?: Evaluating structural correspondences between color similarity judgments using unsupervised alignment - Genji Kawakita; Ariel Zeleznikow-Johnston; Ken Takeda; Naotsugu Tsuchiya; Masafumi Oizumi (iScience)
Summary: Whether one person’s subjective experience of the “redness” of red is equivalent to another’s is a fundamental question in consciousness studies. Intersubjective comparison of the relational structures of sensory experiences, termed “qualia structures”, can constrain the question. We propose an unsupervised alignment method, based on optimal transport, to find the optimal mapping between the similarity structures of sensory experiences without presupposing correspondences (such as “red-to-red”). After collecting subjective similarity judgments for 93 colors, we showed that the similarity structures derived from color-neurotypical participants can be “correctly” aligned at the group level. In contrast, those of color-blind participants could not be aligned with color-neurotypical participants. Our results provide quantitative evidence for interindividual structural equivalence or difference of color qualia, implying that color-neurotypical people’s “red” is relationally equivalent to other color-neurotypical’s “red”, but not to color-blind people’s “red”. This method is applicable across modalities, enabling general structural exploration of subjective experiences.